Effect of tidal level and season oN the community structure of bivalves at a mangrove plantation in Barrido, Ajuy, Iloilo. - Trespeces, Althea Guanco
The mangrove plantation in Barrido, Ajuy was established in March 2003 and is protected from gleaning by residents who occasionally collect shellfish for food. This study thus aimed to provide baseline information on the bivalves occuring in the plantation and to determine the effects of tidal level and season on the community structure of bivalves in the area., Four bivalves species, Galfrarium tumidum, Ruditapes variegatus, Katelysia hiantina (Veneridae) and Septifer bilocularis (Mytilidae) were found to occur in Plot 1 of the mangrove plantation and in the adjacent non-mangrove area. R. variegatus dominated all tidal levels in both mangrove and non-mangrove areas during both dry and wet seasons. Bivalve density was found not to be dependent on organic matter concnetration and sorting index of the sediment. The most obvious factor affecting bivalve density was the tidal level. Highest overall density occured in the low intertidal region of both mangrove and non-mangrove areas sampled. Some filter-feeders do not thrive high in the intertidal because they are not submerged sufficiently enough to give them time to feed. Moreover, mean density was greater during the dry season compared to the wet season. During the dry season, mean density was greater in the mangrove area than in the non-mangrove area. During the wet season however, the reverse was true.